Characterizations of Faintly $(τ_1,τ_2)$-continuous functions (European Journal of Pure and Applied Mathematics, 2024)
This paper deals with the concept of faintly $(τ_1,τ_2)$-continuous functions. Furthermore, some characterizations of faintly $(τ_1,τ_2)$-continuous functions are investigated.The relationships between faint $(τ_1,τ_2)$-continuity and other forms of $(τ_1,τ_2)$-continuity are considered.
Keywords: $(τ_1,τ_2)θ$-open set; $(τ_1,τ_2)θ$-closed set; faintly $(τ_1,τ_2)$-continuous function